Resetting Sistem Proteksi Pada Sistem Kelistrikan PT. Sasa Inti - Gending Plant - Misbahul Munir; Muhammad Rifqi Zhuliansya (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Sasa Inti Ltd.-Gending Plant intends to increase the load on its electrical system to support factory production activities. Therefore, it is necessary to reset the protection system in the existing electrical system or after planning for additional loads. In addition to resetting the protection system, an evaluation of short-circuit current is also needed for this research. The coordination of the protection system between phase fault relay and ground fault relay was simulated using ETAP software. The results of resetting the protection system would be used to secure the electrical system in the existing system as well as in the planning to increase the load appropriately, reliably, and well at Sasa Inti Ltd.-Gending Plant.Keywords: resetting, short circuit, protection system coordination, ETAP, existingSasa Inti Ltd.-Gending Plant intends to increase the load on its electrical system to support factory production activities. Therefore, it is necessary to reset the protection system in the existing electrical system or after planning for additional loads. In addition to resetting the protection system, an evaluation of short-circuit current is also needed for this research. The coordination of the protection system between phase fault relay and ground fault relay was simulated using ETAP software. The results of resetting the protection system would be used to secure the electrical system in the existing system as well as in the planning to increase the load appropriately, reliably, and well at Sasa Inti Ltd.-Gending Plant.Keywords: resetting, short circuit, protection system coordination, ETAP, existing